Tasawuf dalam Cengkeraman Materialisme Historis: Kajian Pemikiran Husein Muruwwa - Abdul Kadir Riyadi (Jurnal Theologia, 2020)
By referring to the thought of Husain Muruwwa, this study looks at the spiritual dimension of Islam, namely Tasawuf, and how it is being interpreted in terms of a continuous social change. Muruwwa –the paper tries to show- is confident that the only authentic approach to interpreting Islam and Tasawuf in terms of social change is historical materialism, which he often calls intellectual Marxism or Realist Socialism. The advantage of this approach, he argues, lies in its ability to rejuvenate the missing intellectual dimension of Islam, but also in its capacity to produce knowledge as well as in establishing the link between the past and the present. The whole idea of the link between the past and the present is associated with his project to formulate what he calls, a new national culture. While believing that Islam can be a vibrant source of the new culture, he treats this religion as a form of culture as such. Hence –this paper shows- Muruwwa’s notion of Islam is quite heterodox since he tries to drag out its theological dimension in order to dig up its social aspects. His view of Tasawuf is equally uncommon. His is the idea that Tasawuf has nothing to do with Islam. It is rather the product of social interaction in a particular society. Being Marxist Moreover, he maintains that the central teaching of the Sufis is not to encourage men to know God but to become God as such.